Kesalahan Penggunaan Kata Bilangan “二ER” dan“两LIANG” oleh Siswa Kelas VII SMP Wahidin T.A. 2023/2024 - Alwiyah Rahmatika; Natasyia Natasyia (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to analyze the errors in the use of the numerals "er" and "liang" by class VII students of SMP Wahidin in the academic year 2023/2024. This study uses a qualitative research method with elicitation and interview techniques to describe the types of errors and factors causing errors made by class VII students of SMP Wahidin in the academic year 2023/2024. The results of the data analysis prove that students still make many mistakes in using the numerals "er" and "liang". The types of errors made by class VII students of SMP Wahidin when using the numerals "er" and "liang" consist of 178 selection errors, 80 sequencing errors, 4 addition errors and 2 subtraction errors. While the factors causing errors consist of mother tongue interference as many as 12 people, lack of discussion of the material as many as 2 people, Mandarin language learning strategies as many as 2 people and teachers who are not serious in teaching as many as 8 people.